Pengaruh Kepercayaan Merek, Kualitas Produk Dan Word Of Mouth Terhadap Keputusan Pembelian Kopi Nescafe Di Kota Ambon - Merry Margareth Pelupessy; Erlinda Tehuayo; Steven Ruhulessin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to examine the effect of brand trust, product quality and word of mouth on purchasing decisions for Nescafe coffee in Ambon City, with a sample of 124 respondents who were determined using the purposive sampling method, using the research method is a quantitative method with multiple linear regression analysis and processing using the SPSS application. The results showed: (1) Brand Trust has a significant effect on purchasing decisions. (2) Product quality has a significant effect on purchasing decisions. (3) Word of mouth has a significant effect on purchasing decisions.